RETRACTED: Construction clusters in the regional economy: Spatial dimension and indicators of strategic development - Abdullayev Ilyоs; Barmuta Karine; Akhmetshin Elvir; Klochko Elena (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001